“COMEÇAR DE NOVO”: PROCESSO DE INTEGRAÇÃO/REINTEGRAÇÃO NO MERCADO DE TRABALHO DAS ALUNAS DO PROEJA DO INSTITUTO FEDERAL DE MINAS GERAIS | “Start again”: integration / reintegration process in the labor market of the women students of the PROEJA of the Instituto Federal de Minas Gerais (Trabalho & Educação, 2017)
This research intends to study the insertion or the graduated female students, that have 40 years old or more, of PROEJA – National Program of the Professional Education Integration with the Basic Education in the Young and Adults Education Mode, of IFMG - Federal Institute of Minas Gerais, in the labor market. The asymmetries and hierarchies related to the presents genders in today’s labor market show real contextualization of gender in one moment that social indicators points to a population getting older in many countries. The experience and production of the gender in historical, social and cultural context is the result of established norms, considering that this set of rules suffers changes according to time and place. The class, race, generation, ethnicity and nationality are crossed with gender, and, so establish themselves concepts related to female and male participation in the public world, and, particularly discussed here, in the labor market. The inclusion of “not young” women, pointed by IBGE, in the...___Esta pesquisa se propõe a estudar a inserção das alunas egressas, com 40 anos ou mais de idade, do PROEJA – Programa Nacional de Integração da Educação Prossional com a Educação Básica na Modalidade de Educação de Jovens e Adultos –, do IFMG – Instituto Federal de Minas Gerais –, no mercado de trabalho. As assimetrias e hierarquias relacionadas aos presentes sexos, no mercado de trabalho da atualidade, demonstram contextualizações reais do gênero num momento em que indicadores sociais apontam para o envelhecimento da população em diversos países. A vivência e produção do gênero no contexto histórico, social e cultural é resultado de normatizações estabelecidas sendo que tal conjunto de normas sofre alterações de acordo com o tempo e o lugar. A classe, a raça e a geração interseccionalizam com o gênero e assim estabelecem contextos próprios relacionados à participação feminina e masculina no mundo público e, particularmente discutido aqui, na educação prossional e no mercado de trabalho. A inserção de mulheres “não jovens”, apontada pelo IBGE, no...